Total Phenolic Content, Antioxidant Activity, Some Physical and Chemical Properties of Pestil - SENGÜL*, MEMNUNE; YILDIZ, HILAL; GÜNGÖR†, NEVA; OKÇU, ZÜHAL (Asian Journal of Chemistry, 2024)
The objective of the present investigation is to determine total phenolic content, antioxidant activity, some physical and chemical properties of mulberry pestil (without additive, with glucose, with peanut, with walnut), plum pestil and cornelian cherry pestil. Total phenolic content of the water extracts of pestil samples was estimated as gallic acid equivalents (GAE) by Folin-Ciocalteu method spectrophotometrically. The antioxidant activity of water extracts prepared from pestil samples was measured by β-carotene bleaching method. Total phenolic content was found from 4.79 (mulberry pestil without additive) to 28.36 μg GAE/mg (plum pestil). The antioxidant activity of pestil samples varied from 40.05 % (mulberry pestil without additive) to 90.92 % (plum pestil). Dry matter, ash, protein, total sugar, reducing sugar, sucrose, pH, titratable acidity, colour (L, a, b), thickness of pestil samples were determined between 75.30-87.53 %, 0.18-3.42 %, 2.44-7.35 %, 30.91-54.60 %, 21.38-41.05 %, 0.83-27.54 %, 3.39-5.72 %, 0.06-6.25 % (malic acid); 27.35-41.35, (+1.25)-(+11.50), (+0.99)-(+18.22), 0.57-6.40 mm, respectively. The present study shows that pestil samples had high amount of phenolics content, antioxidant activity, carbohydrates and protein content.